2023
DOI: 10.3847/1538-4357/acf9ee
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Some Galaxy Disks is Still Perplexing

J. A. Sellwood,
R. G. Carlberg

Abstract: The problem of how some disk galaxies avoid forming bars remains unsolved. Many galaxy models having reasonable properties continue to manifest vigorous instabilities that rapidly form strong bars and no widely accepted idea has yet been advanced to account for how some disk galaxies manage to avoid this instability. It is encouraging that not all galaxies formed in recent cosmological simulations possess bars, but the dynamical explanation for this result is unclear. The unstable mode that creates a bar is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…The ratio of vertical to radial dispersions 0.5 (Figure 9c) among the low [α/Fe] stars at, and interior to, the Solar circle is surprisingly low, because cloud scattering should quickly lead to a value of ∼0.6, as predicted by Ida et al (1993) for a flat rotation curve. Their prediction, which took proper account of distant scattering and is in agreement with numerical results (Villumsen 1985, Shiidsuka & Ida 1999, Hänninen & Flynn 2002, Sellwood 2008, is that the equilibrium axis ratio depends weakly on the local slope of the rotation curve, with smaller values for declining, and larger for rising, V c with radius.…”
Section: Age-velocity Dispersion Relationssupporting
confidence: 75%
See 1 more Smart Citation
“…The ratio of vertical to radial dispersions 0.5 (Figure 9c) among the low [α/Fe] stars at, and interior to, the Solar circle is surprisingly low, because cloud scattering should quickly lead to a value of ∼0.6, as predicted by Ida et al (1993) for a flat rotation curve. Their prediction, which took proper account of distant scattering and is in agreement with numerical results (Villumsen 1985, Shiidsuka & Ida 1999, Hänninen & Flynn 2002, Sellwood 2008, is that the equilibrium axis ratio depends weakly on the local slope of the rotation curve, with smaller values for declining, and larger for rising, V c with radius.…”
Section: Age-velocity Dispersion Relationssupporting
confidence: 75%
“…Simulations by Sellwood (2011) of one of the cases presented by Bertin et al (1989) confirmed that a single, slowly growing mode was present when disturbance forces were restricted to m = 2. The basic state of the collisionless particle disk did not evolve in this restricted simulation while the mild instability grew slowly.…”
Section: Quasi-steady Density Wavesmentioning
confidence: 78%
“…With simulations it is difficult to produce an unbarred twoarmed galaxy, since a massive disk tends to be unstable to bar formation (Efstathiou et al 1982;Bottema 2003;Fujii et al 2018), and a massive halo tends to suppress both bar formation and the formation of a two-armed spiral (Sellwood et al 2019;Sellwood 2023). A possible way to prevent bar formation is by adding a classical bulge (Sellwood 1985).…”
Section: Comparison With Theories Of Spiral Arm Production and Mainte...mentioning
confidence: 99%